Image_6.jpg - Mumbai Archive Project Team (Jio Institute, 2024)
The base ingredient for making tandalachi bhakri is rice flour, which is made from a special variety of rice. The ladies prepare the flour at home and carry it in containers to the stall where they make the dough fresh.